From Novice to Investor: Uncovering the Role of Self Efficacy, Financial Knowledge and Social Influence on Genz Investment Intention (Journal of Asian Development Studies, 2025)
This study aims to examine the impact of self-efficacy, financial knowledge, and social influence on investment intention among Generation Z in Pakistan. The purpose of this study is to investigate the mediating roles of financial attitude and financial literacy in the relationships between financial attitude, social influence, and self-efficacy, as well as their impact on the intention to invest. This research is quantitative, and we collect data through a questionnaire from Generation Z. The researcher gathered information from 362 respondents through an electronic questionnaire. For date analysis, we utilise SPSS and SmartPLS. The purposive sampling technique is used to acquire data from educated people regarding the topic under analysis. The results of this study show that social influence, self-efficacy, and financial knowledge have a significant positive impact on the intention to invest. Financial attitude significantly mediates the relationship between financial knowledge and social influence in terms of intention to invest. At the same time, it has an insignificant mediating role between self-efficacy and intention to invest. Moreover, financial literacy significantly mediates the relationship between social influence and self-efficacy in terms of intention to invest. This study suggests that financial knowledge, self efficacy, and financial literacy among young investors can promote rational investment behaviour and boost Pakistan's stock market participation, thereby contributing to economic growth.